2023
DOI: 10.1177/15353702231191195
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic strategies to improve liver regeneration after hepatectomy

Hayeong Jeong,
Chanbin Lee,
Min Jae Lee
et al.

Abstract: Chronic liver disease is one of the most common diseases worldwide, and its prevalence is particularly high among adults aged 40–60 years; it takes a toll on productivity and causes significant economic burden. However, there are still no effective treatments that can fundamentally treat chronic liver disease. Although liver transplantation is considered the only effective treatment for chronic liver disease, it has limitations in that the pool of available donors is vastly insufficient for the number of poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 72 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Differences in hypertrophy dynamics of FLR of different sizes were investigated after partial hepatectomies, living liver donors, and partial liver graft recipients. These demonstrated that regeneration depends on body mass, TLV, and FLR (17)(18)(19). In addition, the liver regenerates faster in the recipient than in the donor, which applies to all grafts (left lobe, right lobe, and left lateral section).…”
Section: Discussionmentioning
confidence: 90%
“…Differences in hypertrophy dynamics of FLR of different sizes were investigated after partial hepatectomies, living liver donors, and partial liver graft recipients. These demonstrated that regeneration depends on body mass, TLV, and FLR (17)(18)(19). In addition, the liver regenerates faster in the recipient than in the donor, which applies to all grafts (left lobe, right lobe, and left lateral section).…”
Section: Discussionmentioning
confidence: 90%
“…A study has reported that not only small hepatocytes but also mature hepatocytes express CD44 when the liver is partially removed and mitogenic stimuli are produced [97,98]. The liver exhibits a low rate of cellular turnover, and hepatocytes are mostly found in a quiescent state (G0) of the cell cycle under normal/healthy conditions [99][100][101]. When the liver is injured or partially removed, hepatocytes exit G0 in large numbers and undergo multiple rounds of division simultaneously, showing a remarkable capacity for regeneration.…”
Section: Cd44 Influences Cell Proliferation and Differentiation In Th...mentioning
confidence: 99%
“…This imbalance is greatly responsible for chronic inflammation. In elderlies [ 42 ] and individuals with metabolic disorders [ 43 ], mitochondrial dysfunction occurs alongside reduced activity of antioxidant enzymes, leading to heightened ROS levels. ROS is responsible for harmful effects on lipids, proteins, and nucleic acids, including DNA.…”
Section: Introductionmentioning
confidence: 99%
“…Memory and other cognitive processes may be affected when metabolic disorders interfere with the brain’s energy metabolism [ 43 ].…”
Section: Introductionmentioning
confidence: 99%